A dual control mechanism synchronizes riboflavin and sulphur metabolism in Bacillus subtilis - Pedrolli, Danielle Biscaro [UNESP]; Kühm, Christian; Sévin, Daniel C.; Vockenhuber, Michael P.; Sauer, Uwe; Suess, Beatrix; Mack, Matthias (Proceedings of the National Academy of Sciences, 2015)
Flavin mononucleotide (FMN) riboswitches are genetic elements, which in many bacteria control genes responsible for biosynthesis and/or transport of riboflavin (rib genes). Cytoplasmic riboflavin is rapidly and almost completely converted to FMN by flavokinases. When cytoplasmic levels of FMN are sufficient (high levels), FMN binding to FMN riboswitches leads to a reduction of rib gene expression. We report here that the protein RibR counteracts the FMN-induced turn-off activities of both FMN riboswitches in Bacillus subtilis, allowing rib gene expression even in the presence of high levels of FMN. The reason for this secondary metabolic control by RibR is to couple sulfur metabolism with riboflavin metabolism.
Keywords: Bacillus subtilis; Fmn riboswitch; Ribr; Flavin mononucleotide; Riboflavin